Impact of the MELD Scale on Hospital Admissions for Hepatocarcinoma (2000 to 2018), Brazil - Mercês Silva, Alexandro das (Journal of Community Medicine and Health Solutions, 2025)
Background: The health professional appears to be concerned given the number of questions surrounding the patient’s post-transplant survival, patient selection method, and the continuous search for scores that reflect their reality and reconcile the results they desire with the patient’s expectations. It is from these considerations that the present work was born with the purpose of understanding the reality of patients hospitalized for hepatocellular carcinoma and what adherence to the Model For End-Stage Liver Disease (MELD) criteria meant in Brazil. Methods: This study is a discrete, univariate time series on emergency hospitalizations that occurred between 2000 and 2018, in the city of São Paulo, Brazil. Python version 3.11 was the software used for statistical treatment and analysis of the time series. Results: There were 6887 hospitalizations for malignant neoplasm of liver and intrahepatic bile ducts, in the period 2000-2006, of which 2898 were elective and 3915 (56.85%) were urgent in the period. There was an increase of 63.97% in the number of emergency hospitalizations in relation to the period 2000-2006 and 2007-2013. To highlight, in 2013 there were 1270 emergency admissions, which represented an increase of 109.22% in relation to the number of emergency admissions in 2006. The contingency correlation analysis demonstrated a significant association between the variables in which the chi-square value was 82.18, the p-value was 1.24 x 10-19, and the critical value was 3.84 with one degree of freedom. There was a 123.65% increase in the number of hospitalizations for chronic hepatitis, not elsewhere classified, between the periods 2000-2006 and 2007-2013. The chi-square value of the contingency association was 221.22, with a p-value of 4.90 x 10-50, a critical value of 9.488, with a significance level of 5% and one degree of freedom. The study showed an increase in hospitalizations of 21.88% for alcoholic liver disease between the periods 2000-2006 and 2007-2013. In the period 2000-2006, there were 21330 hospitalizations, 19224 of which were urgent (90.13%). In the period 2007-2013, there were 25997 hospitalizations, of which 22,802 (87.71%) occurred urgently. The chi-square value was 68.95, the p-value was 1 x 10-16, and the critical value was 3.84, with one degree of freedom. Conclusion: The MELD score, as it is sensitive to the patient’s severity, selects those who are at an advanced stage of the disease for liver transplantation. In this scenario, patients do not necessarily have access to outpatient services and begin to attend them regularly when MELD identifies the advanced stage of the disease, opening a gap between prevention, treatment, and rehabilitation.